Răspunsuri

2014-03-16T10:44:53+02:00
6+{8*[4+2x/6]-37}*14=48
6+[8*(4+xsupra 3)-37]*14=48
6+[8*12+x supra 3 -37]*14=48
6+(96+x-11 totul supra 3)*14=48
6+(x-15 supra 3)*14=48      >>>amplifici cu 3 la 6 de la inceput si la 48 de la sfarsit
si iti da:
18+(x-15)*14=144
18+14x-210=144
14x=192+144
14x=336
x=336/14
x=24
 


1 1 1
2014-03-16T10:56:15+02:00
{8*[4+(2*x)/6]-37}*14=48-6=42
{8*[4+(2*x)/6]-37}=42:14=3
8*[4+(2*x)/6]=37+3=40
4+(2*x)/6=40:8=5
(2*x)/6=1
2*x=6*1=6
x=6:2=3
Verificare
6+{8*[4+(2*3)/6]-37}*14=48





1 5 1